Promoting your school : going beyond PR - Warner, Carolyn. 4 0 16; 5 (Thousand Oaks, CA : Corwin Press, 2009)
Describes strategies that may be used by principals and administrators to help promote their schools, increase public confidence, and improve communications, and includes reproducible forms, handouts, and checklists.
Includes bibliographical references.
Professional;Professional
Keywords: 2 -- 0; 6; Public relations;Public relations. -- Schools;Schools -- United States.;United States; 20; 2